Designing an Interdisciplinary TEL Framework Linking Islamic Studies, Social Studies, and English Proficiency for Sustainable Entrepreneurship - Gaji Maiwada Abubakar; Zubaida Yahya Ahmad; Adamu Abubakar Muhammad; Abdulkareem Tijjani Ahmad; Nafisa Kabir Galadanci (PT. Student Rihlah Indonesia, 2026)
Entrepreneurship education in underdeveloped countries frequently emphasizes technical skills while undervaluing ethical reasoning, civic awareness, and communication abilities, limiting sustainability and inclusion. Although technology-enhanced learning (TEL) has gained popularity, current research focuses on entrepreneurial skill development in isolation, with little empirical integration of Islamic moral economy, Social Studies pedagogy, and English communication instruction. This study fills that gap by assessing an interdisciplinary TEL framework aimed to promote holistic entrepreneurial competences in Northern Nigeria. The study used a mixed-methods quasi-experimental approach and included 240 students and 24 teachers from secondary and postsecondary institutions. It compared a 12-week TEL intervention group (n=120) to a regular instruction group (n=120). Data were gathered using structured surveys, semi-structured interviews, and classroom observations, then analyzed using t-tests, ANOVA, regression analysis, and thematic coding with triangulation. TEL participants showed statistically significant improvements in self-reported entrepreneurial intention, ethical reasoning, digital literacy, and communication confidence. Qualitative data also indicate increased participation in ethical discussion, collaborative problem-solving, and digital business simulations. While the findings are context-specific and somewhat self-reported, they highlight the ability of interdisciplinary TEL models to improve inclusive and value-driven entrepreneurship education in resource-constrained contexts.